Akibat Hukum Peralihan Hak Atas Objek Sengketa Tanah - lubis, Diana (Universitas Medan Area, 2024)
This article or paper aims to analyze the responsibilities and obligations of a Notary/PPAT in making land sale and purchase deeds, as well as assess the validity of the deed based on the fulfillment of material and formal requirements, as well as provide recommendations to prevent errors and improve the quality of Notary/PPAT services. This research is descriptive, secondary data includes literature materials such as laws and regulations, legal documents, related literature, and the results of previous research. This study uses a normative juridical approach by analyzing secondary legal materials. The data were analyzed qualitatively to identify patterns, gaps, and relevance between legal theory and its practice, using content analysis techniques against regulations, documents, and literature. The results of the study show that the sale and purchase of land require the role of a Notary/PPAT to ensure that the deed is per the law. Its duties include document verification, land legality, and agreement recording. Negligence may lead to the invalidation of the deed, lawsuit, or sanctions. The validity of the act depends on the material and formal requirements. Notary Professionalism guarantees legal certainty and protects the rights of the parties.